TI_GERICHTE 12.2005.144 vom 24. Februar 2006 , Garanzia bancaria o fideiussione - blocco cautelare del suo pagamento - TI Tribunale d'appello (2006)
Garanzia bancaria o fideiussione - blocco cautelare del suo pagamento